Fiqh Science Factors of Difference of Opinion (Analysis of the Relationship with Humans and Its Nature of Needs) - Riyandi S. (Budapest International Research and Critics University, 2021)
Islam is a religion of rahmatan lil'alamin, in which various kinds of religious laws have been regulated, ranging from social issues to spiritual issues, where legal issues relating to humans are wrapped in a scientific discipline, namely the science of fiqh. This phenomenon can be seen clearly from the works of previous scholars, in which one of the problems of Islamic law is worship, mu'amalat munakahat and jinayat or in fiqh it is called rubu 'systematically structured science, this paper discussing the science of fiqh and the factors for the occurrence of differences of opinion among the imams school, the author uses a qualitative methodology using a historical opproach approach in order to provide data validity about the development of fiqh science. History records that fiqh has appeared since the time of Rasulullah SAW (fiqih waqi’ amali) and the time of the Companions. Fiqh developed gradually and preodised until it became a discipline rich in its ushul fiqh methodology. The main factor in the emergence of differences of opinion among the Imam of the Schools was due to their differences in translating Nash Al-Qur'an and Hadith as well as legal issues that were not contained in the Nashnya in the Al-Qur'an or Hadith by focusing on one discipline of Ushul Fiqih through the istimbat methodology through the Ijtihad of each Imam School. The relationship between fiqh and human deeds is always contaminated and cannot be separated from the problem of worship, because humans began at the time when they were subjected to the law of syara ', like it or not, humans have to deal with legal issues (khitabullah). The essence of human need is to get a life that is truly holy in the world and the hereafter, when viewed from the real side of life, humans need a life that is safe, peaceful, prosperous, just and safe. This can be felt and enjoyed if the human has knowledge.